2020
DOI: 10.1016/j.parepi.2020.e00171
|View full text |Cite|
|
Sign up to set email alerts
|

Trypanosoma cruzi infection in domestic and synanthropic mammals such as potential risk of sylvatic transmission in a rural area from north of Antioquia, Colombia

Abstract: In Colombia, dogs and opossum are the most important mammals in domestic and sylvatic T. cruzi transmission. However, the role of both species has not been evaluated in areas where both species converge in the peridomestic area. To evaluate the infection status of domestic and wild mammals in peridomestic habitats of Puerto Valdivia, Antioquia Department. The infection of domestic dogs and small wild mammals was performed by hemoculture, molecular and serological methods. Additionally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
2
14
1
Order By: Relevance
“…Throughout Latin America, T. cruzi infection rates in D. marsupialis range between 3% to over 80% ( Herrera and Urdaneta-Morales, 1992 ; Grisard et al, 2000 ; Pinto et al, 2006 ; Rodriguez-Mongui et al, 2019 ; Magalhães et al, 2021 ). T. cruzi infection rates in our study are similar to opossums from rural landscapes of Costa Rica ( Zeledón et al, 1970 ), the Brazilian Amazon ( Roque et al, 2013 ; Magalhães et al, 2021 ), Colombia ( Cantillo-Barraza et al, 2015 , 2020 ; Rodriguez-Mongui et al, 2019 ) and Venezuela ( Herrera and Urdaneta-Morales, 1992 ; de Lima et al, 2006 ).…”
Section: Discussionsupporting
confidence: 80%
“…Throughout Latin America, T. cruzi infection rates in D. marsupialis range between 3% to over 80% ( Herrera and Urdaneta-Morales, 1992 ; Grisard et al, 2000 ; Pinto et al, 2006 ; Rodriguez-Mongui et al, 2019 ; Magalhães et al, 2021 ). T. cruzi infection rates in our study are similar to opossums from rural landscapes of Costa Rica ( Zeledón et al, 1970 ), the Brazilian Amazon ( Roque et al, 2013 ; Magalhães et al, 2021 ), Colombia ( Cantillo-Barraza et al, 2015 , 2020 ; Rodriguez-Mongui et al, 2019 ) and Venezuela ( Herrera and Urdaneta-Morales, 1992 ; de Lima et al, 2006 ).…”
Section: Discussionsupporting
confidence: 80%
“…A different scenario has been reported in Brazil, where dogs are considered to have little epidemiological importance (Jansen and Roque, 2010). These eco-epidemiological differences also have been observed in Colombia (Ramirez et al, 2013;Jaimes-Dueñez et al, 2017;Cantillo-Barraza et al, 2020b). The results of this work suggested that domestic dogs have an important role in the maintenance of T. cruzi peridomestic transmission cycle in the study area.…”
Section: Discussionsupporting
confidence: 80%
“…Also, dogs were the second most frequent blood source for T. venosa (Jansen and Roque, 2010). Domestic dogs likely constitute the link between the domestic and sylvatic environments, as reported in other Colombian regions (Ramirez et al, 2013;Jaimes-Duenez et al, 2017;Cantillo-Barraza et al, 2020b). Culturally in Colombia, dogs are used as housing protection and are permanently tied to the housing structure.…”
Section: Discussionmentioning
confidence: 94%
“…However, the epidemiological relevance and the veterinarian importance of infected dogs should be determined in the future. Finally, the presence of infected stray dogs inside the studied BITER is a finding that draws our attention due to the known role of domestic dogs as synanthropic reservoirs that could generate new transmission foci inside BITERs [ 67 70 ].…”
Section: Discussionmentioning
confidence: 99%